Endoscopic Gastrointestinal Anastomosis Using Lumen-apposing Metal Stent (LAMS) for Benign or Malignant Etiologies: A Systematic Review and Meta-Analysis. Issue 7 (August 2021) - Hakim, Seifeldin; Khan, Zubair; Shrivastava, Ashish; Koroglu, Emine; Patil, Prithvi; Akyuz, Filiz; Akyuz, Umit; Ramireddy, Srinivas; Badillo, Ricardo; DaVee, Tomas; Thosani, Nirav
Abstract : Background and Aim: Endoscopic gastrointestinal anastomosis using lumen-apposing metal stents (EGAL) is a new technique that is used as an alternative method to bypass benign or malignant strictures. Endoscopists take advantage of 2 bowel loops that are close to each other and place a stent between the lumen of these 2 bowel loops. The authors performed this systematic review and meta-analysis to evaluate the efficacy and safety of this rising procedure. Methods: Electronic database searches were conducted for full eligible articles that were published from the inception to July 2019 using the EGAL procedure to bypass malignant or benign obstruction or to restore bowel integrity after a gastrointestinal altering surgery. The primary outcome of this meta-analysis was to assess efficacy through technical and clinical success. Secondary outcomes were to assess safety through adverse events and to assess the rate of stent maldeployment and the rate of reintervention during the study period. Results: Eight studies were eligible, providing data on 269 patients who underwent 271 EGAL procedures. The median age was 65 years (interquartile range: 63 to 66) with 46% male individuals. Out of 269 patients, 203 underwent EGALs because of malignant etiology and 66 underwent EGAL for benign etiology. The median duration of follow-up was 114 days (interquartile range: 78 to 121). Technical success rate was 94.1% [95% confidence interval (CI), 91.4%-96.9%]. Clinical success rate was 91.4% (95% CI, 88.1%-94.7%). Adverse events rate was 8.5% (95% CI, 4.7%-12.3%). Stent maldeployment rate was 9.5% (95% CI, 3.5%-15.4%) of the total performed EGALs and the reintervention rate was 6.0% (95% CI, 2.3%-9.8%). Conclusion: EGAL procedure has high efficacy and a relatively safe profile and it can be performed in selected patients. Comparison between EGAL and other conventional therapies is difficult because of the lack of randomized trials.